Pengaruh Gaya Kepemimpinan, Kompensasi, dan Pengawasan Terhadap Disiplin Kerja Karyawan di CV. Yudi Putra Medan - Aulia Ramadhan Tanjung; Emi Wakhyuni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the influence of leadership style, compensation, and supervision on employee work discipline at CV Yudi Putra Medan. The type of research used is quantitative through the survey method. The population and sample in this study amounted to 47 employees. The sampling technique used was total sampling. The data collection technique uses a questionnaire. The analysis of the research data used multiple regression analysis carried out using the help of SPSS software. The results of the study show that Leadership Style partially has a positive and significant effect on Employee Work Discipline at CV Yudi Putra Medan with a regression value. Compensation partially has a positive and significant effect on employee work discipline at CV Yudi Putra Medan. Partial supervision has a positive and significant effect on work discipline in CV Yudi Putra Medan, leadership style (X1), compensation (X2), and supervision (X3) simultaneously (together) have a positive and significant effect on Employee Work Discipline